Atividade antifúngica do (+)-a-pineno E (+)-b-pineno isolados e associados sobre Candida spp. de interesse clínico para cavidade bucal - Andrade, Ana Cláudia de Macêdo (2018)
This work was aimed at the evaluation of the antifungal action of isolated and associated (+)-α-pinene and (+)-β-pinene enantiomers on Candida species, their possible mechanisms of action, their molecular interactions with enzymes related to wall formation and fungal cell membrane, as well as its antibiofilm activity. It was used 25 strains of Candida, of clinical origin and of reference, sensitive and resistant to licensed antifungal agents, for determination of Minimum Inhibitory Concentration (MIC), Minimum Fungicide Concentration (CFM), Fraction Inhibitory Concentration Index (ICIF), Microbial Time-kill Curve, possible mechanisms of action, molecular docking and the effect on the inhibition of the biofilm adherence provided by the enantiomers. A descriptive and inferential statistical analysis was performed, considering α=5%. The MIC values ranged from 114.06µM to 7300µM (15.6 µg/mL to 1000µg/mL) and from <57.03 µM to 1825 µM (<7.8 µg/mL to 250µg/mL) for (+)-α-pineno and (+)-β-pineno, respectively. After the association of the evaluated products, it was observed additivity (ICIF = 0.5) and indifference (ICIF = 1.125), when evaluated on strains of C. albicans and C. glabrata, respectively. It was observed that at the MIC and 2xMIC concentrations, (+)-β- pinene was able to reduce significantly (p≤0,05) the fungal growth after 8 hours of incubation. The MIC values of (+)-β-pinene increased 2x for the C. tropicalis and C. krusei strains, when in the presence of 0.8 M sorbitol. In the presence of ergosterol these values remained unchanged, suggesting that this substance acts by means of the inhibition of cell wall synthesis. In the evaluation of the molecular docking simulation, the binding energy values between (+)-β-pinene and enzymes, showed that Delta-14-sterol reductase presented a more stable interaction (−51 kcal/mol), suggesting a probable action on ergosterol biosynthesis. The (+)-β- pinene inhibited 67% of the multi-species biofilm. (+)-α-pinene and especially (+)- β-pinene present effect in vitro on strains of Candida, in planktonic state and organized into biofilms. The action of (+)-β-pinene is probably related to the binding of this molecule to enzymes involved with cell wall formation and ergosterol from fungi of the genus Candida.